Perawatan Sampel Beton dengan Membran Pengering dan Air Pengering Mempengaruhi Kekuatan Tekan Beton di Lab. KAK Kebumen - Aryadi, Haris Tri; Intansari, Dyah Widi Astin (Jurnal Kridatama Sains dan Teknologi, 2025)
The problem that occurs in fresh concrete is the imperfect cement hydration process due to too rapid water loss. This can cause the concrete to become weak, cracked, and not reach the desired compressive strength. The cement hydration process requires sufficient water to react with the cement and form a strong concrete structure. However, if water is lost too quickly due to evaporation, the hydration process cannot take place perfectly. Realizing this problem, we conducted a research experiment to find, compare, and evaluate the effect of various curing techniques on the compressive strength of concrete. The planned concrete quality of 18.68 Mpa was made from a cylinder with a diameter of 15 cm and a height of 30 cm as many as 10 samples. After curing, the concrete was tested twice: soaked in water at 10.19 MPa and 16.98 MPa; doused with water at 11.04 MPa and 11.32 MPa; and wrapped in wet burlap sacks at 8.49 MPa and 10.75 MPa. Treatment wrapped with plastic wrap showed results of 3.96 MPa and 15.28 MPa, while without treatment at outside temperature was 10.47 MPa and 11.32 MPa. The results showed that there was a significant difference in the compressive strength of concrete as measured by the compressive strength of concrete soaked in water for 28 days with treatments of 7 and 28 days respectively. Treatment by soaking in water showed an increase of 54.55% and 90.89%, treatment by sprinkling water increased by 59.10% and 60.59%, treatment by wrapping using wet burlap showed an increase of 45.44% and 57.54%, treatment with plastic wrap increased by 21.19% and 81.79%, while without outdoor treatment had an increase of 56.04% and 60.59%. The results showed that concrete soaked in water for 28 days produced the best compressive strength